2000
DOI: 10.1016/s0925-4439(00)00009-0
|View full text |Cite
|
Sign up to set email alerts
|

The non-oxidative degradation of ascorbic acid at physiological conditions

Abstract: The degradation of L-ascorbate (AsA) and its primary oxidation products, L-dehydroascorbate (DHA) and 2,3-L-diketogulonate (2, 3-DKG) were studied under physiological conditions. Analysis determined that L-erythrulose (ERU) and oxalate were the primary degradation products of ASA regardless of which compound was used as the starting material. The identification of ERU was determined by proton decoupled (13)C-nuclear magnetic resonance spectroscopy, and was quantified by high performance liquid chromatography, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
100
0
5

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(113 citation statements)
references
References 40 publications
5
100
0
5
Order By: Relevance
“…2-Furoic acid 19) was also detected by another HPLC condition. Oxalic acid, which is one of decomposed products of AsA through 2,3-diketogulonic acid in physiological conditions, 26) was not detected in this stored solution. 3OH2P, furfural and 2-furoic acid were derived of AsA through dehydroascorbic acid, 27) while HMF and 5-hydroxymaltol were derived of fructose (data not shown).…”
Section: Effect Of Each Ingredient On the Browning Of Model Solutionmentioning
confidence: 82%
“…2-Furoic acid 19) was also detected by another HPLC condition. Oxalic acid, which is one of decomposed products of AsA through 2,3-diketogulonic acid in physiological conditions, 26) was not detected in this stored solution. 3OH2P, furfural and 2-furoic acid were derived of AsA through dehydroascorbic acid, 27) while HMF and 5-hydroxymaltol were derived of fructose (data not shown).…”
Section: Effect Of Each Ingredient On the Browning Of Model Solutionmentioning
confidence: 82%
“…10) is also solid evidence that this post-translational modification of lysine exists in cataractous lenses. fructose, xylose, erythrulose, glyceraldehyde, glyceraldehyde 3-phosphate, methylglyoxal, 1,3-dihydroxyacetone, and glycolaldehyde are reactive carbonyl compounds known to be able to modify the ⑀ amino group of lysine residues in lens proteins (6,(15)(16)(17)(18)(19)(20)(21). The RP-HPLC analyses showed that none of the above carbonyl compounds was able to produce measurable amounts of OP-lysine when reacted with Boc-Lys at pH 7 for 5 days based on UV and fluorescence HPLC profiles of the reaction mixtures.…”
Section: Op-lysine Is a Newly Identified Advanced Glycation End Productmentioning
confidence: 99%
“…Instead, it was proposed that the protection observed with ascorbate is due solely to its oxidation to dehydroascorbate and, perhaps, subsequent degradation to other products. As dehydroascorbate is extremely unstable in aqueous solution, undergoing facile delactonization to 2,3-diketo-L-gulonic acid, followed by transformation into a large number of products, which include ascorbic acid and erythroascorbic acid [43][44][45][46], it is possible that the effects of dehydroascorbate on LDL oxidation are indirect and are caused by its transformation products. [53] or in the plasma of smokers [54].…”
Section: Introductionmentioning
confidence: 99%